The Differentiation of Corn Choux Pastry Product with Additional Vegetables as Stuffing - Fajri, Ilham; Octavia, Silvi; Ningsih, Caria (Universitas Pendidikan Indonesia, 2020)
Corn is Indonesian's staple food and the need for corn in the country is increasing. This can be seen from the corn fields that are scattered throughout the provinces. This condition has made Indonesia as one of the exporting countries of corn to several ASEAN countries. This study aims to make a differentiation of choux pastry with blended corn in the dough. The research method in this article is experimental. To test the product formulation and product quality, the opinions of the supervisors are employed. Lastly, descriptive test is used, and market analysis of the product is conducted. Samples of choux pastry formulations used the ratios of 50%: 50% and 25%: 75% respectively between wheat flour and corn. Each formulation is tested by the supervisors to produce the average product which is most preferred by the supervisors. Furthermore, the product is tested again using market analysis to find out the public acceptance of the differentiation of corn choux pastry product with the addition of corn.